Odontologia e saúde mental: experiência do PET Saúde no centro de atenção psicossocial álcool e drogas - MOURA, Franciely Araújo (2019)
Aiming to discuss the importance of multi-professional experiences and the role of innovation of “PET – Saúde” on academic background, this paper has as purpose to report the experience of PET Odontology of Federal University of Para (UFPA) with multi-professional group of a “CAPS AD”, in Belem city, state of Para, in the period from December 2016 to August 2017, besides to assess the oral health condition of addicts. This experience presented the integration among different professionals and motivated the development of abilities of odontology students to plain integrated and creative actions to health promotion, through active methodology pointing the new ways to attention health, focusing on the reality of community, and not just the clinical environment. It is understood that the integration among education, services and empowered community by “PET-Saúde” leads to formation in health in a different professional profile, which these professionals became better able to competent to respond the needs of addicts and can be qualified to work in different areas.